Minerals and chelated-based manganese fertilization influences the productivity, uptake, and mobilization of manganese in wheat (Triticum aestivum L.) in sandy loam soils - Dhaliwal, Salwinder Singh; Sharma, Vivek; Shukla, Arvind Kumar; Verma, Vibha; Kaur, Manmeet; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Singh, Prabhjot; Laing, Alison M.; Hossain, Akbar (Frontiers in Plant Science, 2023)
Manganese (Mn) is an essential micronutrient in plants, and it is necessary for hydrolysis in photosystem II, chlorophyll biosynthesis, and also chloroplast breakdown. Limited Mn availability in light soil resulted in interveinal chlorosis, poor root development, and the development of fewer tillers, particularly staple cereals including wheat, while foliar Mn fertilizers were found efficient in improving crop yield as well as Mn use efficiency. In the above context, a study was conducted in consecutive two wheat growing seasons for screening of the most effective and economical Mn treatment for improving the yield and Mn uptake in wheat and to compare the relative effectiveness of MnCO3 against the recommended dose of MnSO4 for wheat. To fulfill the aims of the study, three manganese products, namely, 1) manganese carbonate MnCO3 (26% Mn w/w and 3.3% N w/w), 2) 0.5% MnSO4·H2O (30.5% Mn), and 3) Mn-EDTA solution (12% Mn), were used as experimental treatments. Treatments and their combinations were as follows: two levels of MnCO3 (26% Mn) @ 750 and 1,250 ml ha−1 were applied at the two stages (i.e., 25–30 and 35–40 days after sowing) of wheat, and three sprays each of 0.5% MnSO4 (30.5% Mn) and Mn-EDTA (12% Mn) solution were applied in other plots. The 2-year study showed that Mn application significantly increased the plant height, productive tillers plant−1, and 1,000 grain weight irrespective of fertilizer source. The results of MnSO4 for grain yield wheat as well as uptake of Mn were statistically at par with both levels (750 and 1,250 ml ha−1) of MnCO3 with two sprays at two stages of wheat. However, the application of Mn in the form of 0.5% MnSO4·H2O (30.5% Mn) was found more economical than MnCO3, while the mobilization efficiency index (1.56) was found maximum when Mn was applied in MnCO3 with two sprays (750 and 1,250 ml ha−1) in the two stages of wheat. Thus, the present study revealed that MnCO3 can be used as an alternative to MnSO4 to enhance the yield and Mn uptake of wheat.